The Relationship Between Preschoolers' Attitudes and Play Behaviors Toward Classmates With Disabilities. (May 2015) - Yu, SeonYeong; Ostrosky, Michaelene M.; Fowler, Susan A.
This study was conducted to examine the relationship between 32 typically developing preschoolers' attitudes and play behaviors toward their classmates with disabilities or developmental delays. Children's attitudes toward peers with disabilities were assessed using three methods: child interviews, sociometric peer ratings, and a social acceptance scale. Children's play behaviors (e.g., solitary, onlooker, parallel play, associative/cooperative play) and teachers' involvement in children's play were observed during free play over a 10-week period. Results revealed that children's identification of a classmate with an Individualized Education Program (IEP) as having a disability was negatively related to their associative/cooperative play with the classmate. Typically developing children's sociometric ratings of classmates with disabilities were positively related to their associative/cooperative play with classmates with disabilities. In addition, children's sociometric ratings were a stronger indicator of whether a typically developing child would play with a classmate with a disability than was identification of a classmate as having a disability. Suggestions for future research and implications for practice are discussed.